2012
DOI: 10.1159/000339424
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Induces the Apoptosis of Acute Promyelocytic Leukemia Cells via the Downregulation of Survivin Expression

Abstract: Background and Aims: Bufalin is a cardiotonic steroid isolated from the Chinese toad venom preparation Chan’su and has been shown to induce leukemia cell differentiation and apoptosis under certain experimental conditions. However, the detailed mechanism by which bufalin induces the apoptosis of acute promyelocytic leukemia cells is largely unexplored. Methods: The acute promyelocytic leukemia cell line NB4 was treated with bufalin, then the proliferation was evaluated by cell viability assay and apoptosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Thus, targeting survivin with small-molecule inhibitors by their anti-sense approaches or natural IAP antagonist mimetics may be an attractive strategy of anti-leukemia treatment. Such agents can either directly induce apoptosis of tumor cells or sensitize them to other cytotoxic agents, hence overcoming drug resistance (31,32). Thereofore, the present study evaluated the effect of AA on survivin in HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting survivin with small-molecule inhibitors by their anti-sense approaches or natural IAP antagonist mimetics may be an attractive strategy of anti-leukemia treatment. Such agents can either directly induce apoptosis of tumor cells or sensitize them to other cytotoxic agents, hence overcoming drug resistance (31,32). Thereofore, the present study evaluated the effect of AA on survivin in HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin, one of the major components of the Chinese medicine Chan'Su, was shown to exhibit marked anti-tumor activity against leukemia and various types of solid tumor, including prostate cancer, lung cancer and hepatoma (12)(13)(14)(15)(16)(17)(18)(19). This anti-tumor activity is achieved by inhibition of proliferation and induction of apoptosis (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…This anti-tumor activity is achieved by inhibition of proliferation and induction of apoptosis (18,19). Bufalin was shown to be potent against human OS tissues and cell lines via inducing apoptosis (20,21); however, the specific underlying mechanism has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the similarity in the chemical structure between bufalin and digoxin, bufalin is expected to have a digoxin-like function (5,6). Bufalin has been shown to induce apoptosis in leukemia and solid tumor cells (5)(6)(7)(8)(9)(10). In recent years, studies have revealed that bufalin could effectively inhibit the proliferation of tumor cells, and also assessed its possible molecular mechanism (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%